Perlindungan Hukum Terhadap Hak-Hak Pekerja Akibat Pemutusan Hubungan Kerja Karena Mengundurkan Diri - Sella Petrix Pelupessy; Berd Elkiopas Pelupessy; Sobardo Hamonangan (BULLET : Jurnal Multidisiplin Ilmu, 2025)
The research entitled "Legal Protection of Workers' Rights Due to Termination of Employment Due to Resignation." The purpose of this research is to analyze the substance of labor regulations in Indonesia, particularly regarding the legal protection of workers' rights related to termination of employment due to resignation and the role of government officials in the labor sector in providing legal protection for workers' rights due to termination of employment due to resignation. The research method used is normative law, namely research based on law conceptualized and developed on the basis of the doctrine of positivism which is characterized by lex or lege rather than ius. The type of research conducted, in terms of its form, is descriptive research aimed at obtaining suggestions regarding what should be done to overcome certain problems. The results of this research reveal that the substance of legal protection for workers' rights related to termination of employment due to resignation in Article 162 paragraph (1) is correlated with Article 156 paragraph (4) letter c of Law Number 13 of 2003 concerning Manpower regarding housing replacement and medical treatment. and treatment is set at 15% (fifteen percent) of severance pay and/or long service award money, the formulation is still incomplete and broad (comprehensive), thus creating legal uncertainty (unpredictable). Therefore, government officials provide a positive nuance and act wisely in responding to the ambiguity of norms related to termination of employment due to resignation, and not make the ambiguity of these norms an opportunity to gain benefits for themselves or their groups, and it is also hoped that the implementing regulations made by the officials will create a fair climate (fairness), where there is equal treatment for all parties related to industrial relations.